2017
DOI: 10.1002/oby.21764
|View full text |Cite
|
Sign up to set email alerts
|

The association between cytomegalovirus infection, obesity, and metabolic syndrome in U.S. adult females

Abstract: CMV infection was found to be associated with unique MetS phenotypes that differ between BMI categories and gender. Seropositive normal-weight females had a higher prevalence of MetS and dyslipidemia, while infection in females with extreme obesity was associated with a more metabolically benign profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 40 publications
1
32
1
Order By: Relevance
“…Clinical observations have displayed that patients with acute Epstein-Barr virus(EBV) infection had lower levels of Apo-AI, HDL-C, TC, Apo B, LDL-C and LP-A compared with their controls [25]. Another study showed that cytomegalovirus(CMV) infection was associated with lower HDL-C in normal-weight females [26].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observations have displayed that patients with acute Epstein-Barr virus(EBV) infection had lower levels of Apo-AI, HDL-C, TC, Apo B, LDL-C and LP-A compared with their controls [25]. Another study showed that cytomegalovirus(CMV) infection was associated with lower HDL-C in normal-weight females [26].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously found that CMV is associated with a flatter cortisol rhythm over the day, and with accelerated telomere shortening over three years (Dowd et al, 2017, Steptoe et al, 2009). CMV also affects metabolic processes, though associations with adiposity are poorly understood (Fleck-Derderian et al, 2017). Associations between CMV seropositivity, SES and central adiposity were therefore assessed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there is evidence of sex differences in both ganciclovir pharmacokinetics and the anti-CMV immune response. [11][12][13][14][15][16][17][18] Thus, female patients have been shown to have a faster ganciclovir clearance, and distinct anti-CMV immunological profiles e.g. higher number of secreting anti-CMV T cells.…”
Section: Introductionmentioning
confidence: 99%